2018
DOI: 10.1016/j.celrep.2018.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an Environment for the Study of Fibrosis: A 3D Human Muscle Model with Endothelium Specificity and Endomysium

Abstract: Highlights d Millimeter-scale model of a vascularized 3D human muscle environment d Endothelial cells acquire organ-specific signature in co-culture with muscle cells d Muscle fibroblasts spontaneously self-assemble an endomysium-like structure d Physiologically relevant 3D model for the study of muscle fibrosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 45 publications
0
70
0
Order By: Relevance
“…For focal adhesion quantification, images of paxillin-stained samples were thresholded (binary images were obtained by selecting the commands "image, adjust, threshold" in the Fiji software; the same value was set for all images referred to the same condition) and the number of paxillin foci identified through the "particle analysis" command using Fiji software. Regarding quantification of the area covered by FAK, lamin A, Nesprin-1, and YAP, images were processed using Fiji software following established protocols (Bersini et al, 2018) (region of interest selection within z-projected stacks; thresholding [binary images were obtained by selecting the commands "image, adjust, threshold"; the same value was set for all images referred to the same condition]; computation of area fraction or mean intensity value of the fluorescent signal). For invasion assay quantification, the cells were live-imaged for 24 h after cell membrane staining with a fluorescent dye.…”
Section: Image Analysis and Quantificationmentioning
confidence: 99%
“…For focal adhesion quantification, images of paxillin-stained samples were thresholded (binary images were obtained by selecting the commands "image, adjust, threshold" in the Fiji software; the same value was set for all images referred to the same condition) and the number of paxillin foci identified through the "particle analysis" command using Fiji software. Regarding quantification of the area covered by FAK, lamin A, Nesprin-1, and YAP, images were processed using Fiji software following established protocols (Bersini et al, 2018) (region of interest selection within z-projected stacks; thresholding [binary images were obtained by selecting the commands "image, adjust, threshold"; the same value was set for all images referred to the same condition]; computation of area fraction or mean intensity value of the fluorescent signal). For invasion assay quantification, the cells were live-imaged for 24 h after cell membrane staining with a fluorescent dye.…”
Section: Image Analysis and Quantificationmentioning
confidence: 99%
“…[ 99,132 ] Interestingly, Bersini et al reported on the respecification of primary endothelial cells into muscle‐specific endothelium in their 3D human muscle model, the first study to demonstrate this phenomenon for in vitro endothelial cultures. [ 133 ] Although some studies attempt to use primary vascular endothelial cells, these cells can be heterogenous and are just starting to be characterized in adult human organs. [ 134 ] Recently, the Carmeliet group published a seminal study identifying the single‐cell transcriptional profiles of murine endothelium, demonstrating the heterogeneity in endothelial populations that may provide a key to engineering meso‐ and microscale vascular models and regenerative cues.…”
Section: Meso‐ and Microvascular Engineeringmentioning
confidence: 99%
“…Optimized regimes of biophysical stimulation and combinatorial uses of growth factors, small molecules, and metabolic fuel sources will be needed to accelerate engineered muscle maturation in weeks rather than years [1,6]. Biomimetic incorporation of other muscle-resident cells such as fibroblasts, motor neurons [10], and immune [11] and vascular [12,13] cells will allow more accurate modeling of native muscle composition, function, regeneration, and complex disease phenotypes. Incorporating macrophages, in particular, was critical to successful in vitro and in vivo regeneration of adult rat-engineered muscle, highlighting the increased physiological relevance of multicellular models [11].…”
Section: Expert Opinionmentioning
confidence: 99%